Analysis of Product Diversification Strategy on Sales Volume at a Bakery Company (Lyly Bakery) - Budi Hartono; Abid Muhtarom; Mohammad Yaskun (Jurnal Multidisiplin Sahombu, 2025)
This research aims to find out the Product Diversification Strategy implemented by the Lamongan Lily Bakery Bread Company. To find out whether the Product Diversification Strategy implemented has increased the Sales Volume of the Lamongan Lily Bakery Bread Company. From the results of the data triangulation analysis, it is known that the strategy implemented by the business owner of Roti Lily Bakery to increase sales volume is the product diversification strategy. Based on the analysis conducted by the researcher, the diversification strategy carried out by Roti Lily Bakery is a concentric diversification strategy, where all products produced have a relationship in terms of marketing and technology, namely processed products from cassava, namely cassava chips with various flavor variants and variants of bread shapes. The impact that occurred when implementing the product diversification strategy at Roti Lily Bakery was the advantages and challenges faced. The positive impact or profit obtained by business owners by implementing a product diversification strategy is that this strategy also increases the sales volume of their products. Meanwhile, the challenges faced are constrained by the availability of production raw materials that are sometimes late delivered due to the large demand from other companies, tools to produce new products that are still limited, and production land as an impact that arises due to the need for a place for new technology, where to create new types of products new technology is also needed.